HSK 以外的汉语新词汇分类 - Wu Liangyu; Low Hiang Loon; Goh Ying Soon (Sinolingua: Journal of Chinese Studies, 2025)
As the number of new Chinese vocabulary increases year by year, mastering new vocabulary beyond the HSK (Global Chinese Proficiency Test) syllabus is crucial to improving the overall language proficiency of international students. However, international students face many challenges in understanding new Chinese vocabulary, including emotional tendencies, personal abilities, and the complexity of Chinese vocabulary. Among them, the biggest challenge comes from the aspect of vocabulary. Specifically, the most prominent problems faced by international students in learning new Chinese vocabulary include the complexity of vocabulary, the lack of a systematic learning method, the difficulty in identifying vocabulary with multiple meanings, and the difficulty in inferring their meaning based on existing knowledge. Therefore, it is particularly important to systematically learn the classification and characteristics of new Chinese vocabulary. Based on the two dictionaries of "Chinese New Vocabulary 2018" and "Chinese New Vocabulary 2019-2020", this study categorizes Chinese new vocabulary into Analogy, Simulation, Metaphor, Neologism, Old Vocabulary with New Meanings and Abbreviations. The study aims to comprehensively analyze its classification and characteristics and provide valuable guidance for international students' vocabulary learning. The classification of Chinese new vocabulary beyond HSK not only helps to improve the overall language proficiency of international students, but also deepens the academic community's understanding of the characteristics of Chinese new vocabulary learning and provides an important reference for future related research.